Quantifying Learning: Measuring Student Outcomes in Higher Education in England - Camille Kandiko Howson; Alex Buckley (Politics and Governance, 2020)
Since 2014, the government in England has undertaken a programme of work to explore the measurement of learning gain in undergraduate education. This is part of a wider neoliberal agenda to create a market in higher education, with student outcomes featuring as a key construct of value for money. The Higher Education Funding Council for England (subsequently dismantled) invested £4 million in funding 13 pilot projects to develop and test instruments and methods for measuring learning gain, with approaches largely borrowed from the US. Whilst measures with validity in specific disciplinary or institutional contexts were developed, a robust single instrument or measure has failed to emerge. The attempt to quantify learning represented by this initiative should spark debate about the rationale for quantification—whether it is for accountability, measuring performance, assuring quality or for the enhancement of teaching, learning and the student experience. It also raises profound questions about who defines the purpose of higher education; and whether it is those inside or outside of the academy who have the authority to decide the key learning outcomes of higher education. This article argues that in focusing on the largely technical aspects of the quantification of learning, government-funded attempts in England to measure learning gain have overlooked fundamental questions about the aims and values of higher education. Moreover, this search for a measure of learning gain represents the attempt to use quantification to legitimize the authority to define quality and appropriate outcomes in higher education.